Pedagogi filoeirene: Ajakan untuk mencintai perdamaian dalam kemajemukan - Sopakua, Samel; Hasugian, Johanes Waldes (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2022)
Hate speech and invitations to be hostile to adherents of other religions and beliefs are becoming a strengthening phenomenon today. Intolerance and radicalism that lead to violence and social conflict are increasingly arbitrary. This hostility occurs in the world of education, teachers and students are exposed to ideas that are contrary to the values of Pancasila and religious norms. Religious moderation as an effort to deradicalize through religious education, especially Christian religious education, is gaining momentum to instill peace-loving values in students. To achieve this, Christian religious education exists and participates in and through it. Various sources of literature or literature study to explore the data, with qualitative-descriptive research were conducted to find a picture of the philoeirene model in Christian religious education and to actualize the education of peace-loving attitudes in students. This study found that a comprehensive, basic, or deep and deeply rooted understanding of the concepts of peace and philoeirene is not an option but is imperative in nature to be instilled in every student. Strengthening contextual or relevant curriculum and commitment to implementing a peace-loving attitude is praxis in Christian religious education in a pluralistic society. AbstrakUjaran kebencian dan ajakan untuk memusuhi penganut agama dan kepercayaan lain menjadi fenomena yang menguat dewasa ini. Intoleransi dan radikalisme yang berujung pada kekerasan dan konflik sosial semakin semena-mena. Sikap permusuhan tersebut terjadi di dunia pendidikan, guru dan murid terpapar pada paham yang bertentangan dengan nilai Pancasila dan norma agama. Moderasi beragama sebagai upaya deradikalisasi melalui pendidikan agama, khususnya pendidikan agama Kristen mendapat momentum untuk menanamkan nilai cinta damai dalam diri peserta didik. Untuk mewujudkan hal tersebut pendidikan agama Kristen hadir dan berpartisipasi di dalam dan melaluinya. Berbagai sumber literatur ataupun studi pustaka untuk mengeksplorasi data, dengan penelitian kualitatif-deskriptif dilakukan untuk menemukan gambaran model filoeirene dalam pendidikan agama Kristen, serta mengaktualisasikan pendidikan sikap cinta damai dalam dalam diri peserta didik. Penelitian ini menemukan bahwa pemahaman yang komprehensif, mendasar atau mendalam serta mengakar kuat berkenaan dengan konsep perdamaian dan filoeirene bukan opsi namun bersifat imperatif ditanamkan bagi setiap peserta didik. Penguatan kurikulum yang kontekstual atau relevan dan komitmen dalam mengimplementasikan sikap cinta damai merupakan suatu praksis dalam pendidikan agama Kristen di tengah masyarakat majemuk.